Post-feminist Discourses in Taylor Jenkins Reid’s The Seven Husbands of Evelyn Hugo - Liyana Khairunnisa; Supiastutik Supiastutik; Ghanesya Hari Murti (Universitas Sanata Dharma, 2024)
This research analyzes feminist success in post-feminist discourse related to neoliberalism in the Hollywood film industry through The Seven Husbands of Evelyn Hugo. This research aims to reveal how Evelyn's actions within the neoliberalism framework criticize the discourse of post-feminism. Postfeminism emerged as a response to feminism, suggesting that women can embrace traditional feminine roles while still feeling empowered and in control, as post-feminism believes that feminism has largely achieved its goals. Angela McRobbie's post-feminism theory is used to analyze the novel because it identifies the form of neoliberal practice in post-feminism. The results show that the success of neoliberal feminists portrayed by Evelyn is false because the dominance of neoliberalism practices still idealizes a heterosexual matrix with seven marriages possible in the Hollywood industry. Women are capitalized as sexual objects for heterosexual audiences for neoliberal interests. Women must comply with these two things through the sexual contract by participating in the fashion beauty complex to survive in the work environment. The resulting impact is that women then repress their gender identity and discipline it to fit the industry's logic. This discourse is disseminated in the novel as a social discourse even though the author's critical position seeks to reject the application of heteronormativity in the novel and also the social practices of the Hollywood industry.